Fresh Meat Selection for Consumers - Chad Carr; Ed Jennings; Larry Eubanks (EDIS)
AN229, a 5-page illustrated fact sheet by Chad Carr, Ed Jennings, and Larry Eubanks, aims to provide consumers with a solid working knowledge of fresh meat terminology so that they can select meat cuts that will perform desirably in all recipes. Includes references. Published by the UF Department of Animal Science, October 2009.